PRAKTIK MEDIA PR INTERNAL DALAM DIVISI MARKETING SUPPORT PT KENCANA MAJU BERSAMA - Sumiati; Mohammad Insan Romadhan (Sintesa, 2026)
Internal PR media practices are an important part of supporting work coordination, information dissemination, and effective internal relations within an organization. This study aims to describe the internal PR media practices in the Marketing Support Division of PT Kencana Maju Bersama by utilizing empirical data from an undergraduate thesis on organizational communication within the division. The study used a descriptive qualitative approach with observation, interviews, and documentation as data collection techniques. The research subjects included managers, supervisors, and staff in the Marketing Support Division. The findings show that internal PR media practices in this division are carried out through formal and informal communication channels, both direct and work-based internal media, to support briefings, task coordination, direction delivery, evaluation, and cross-functional problem solving. The supervisor acts as the main connector in internal message distribution, while communication among employees and across divisions reflects the integrative role of internal media in strengthening teamwork. These internal PR media practices contribute to work quality, coordination effectiveness, and employee independence. However, internal information management still faces challenges in terms of work quantity and timeliness due to sudden priority tasks. These findings indicate that structured internal PR media practices can strengthen work processes and support employee performance within the division Keywords: Internal PR Media, Internal Communication, Marketing Support, Employee Performance